Quantitative Evaluation of Chinese Herb Medicine in the Treatment of Sialorrhea and Frequent Nighttime Urination in Patients with Parkinson's Disease. (18th April 2017) - Sun, Chuanhe; Wang, Dandan; Jiang, Wenfei; Liao, Weilong; Gao, Penglin; Pan, Weidong; Liu, Te
Abstract : Aims . To evaluate the efficacy of Lian-Se formula (LSF), one Chinese herb formulation for treating sialorrhea and frequent overnight urination in patients with Parkinson's disease (PD). Methods . 96 PD patients suffering from sialorrhea and/or frequent nighttime urination were divided into two groups: an LSF group ( n = 48) treated with LSF for 6 weeks and a placebo group ( n = 48) treated with a placebo formula whose appearance and taste were the same as LSF for 6 weeks. All patients were treated by standard antiparkinsonism medicine according to the PD guideline of China. The changes of the quantity of saliva (QS) (mL), frequency of nighttime urination (FNU) and early sleep activity (ESA), and nocturnal activity (NA) by analyzing actigraphic records as the primary results and the total score of unified Parkinson's disease rating scale (UPDRS) and the Epworth Sleepiness Scale (ESS) as the secondary results were used to evaluate the clinical efficacy in both groups. Results . There were no significant differences in the baseline values of QS, FNU, NA, ESA, UPDRS total score, and ESS between the two groups. At the end of week 6, the QS, FNU, NA, and ESA in the LSF group showed superior results to those of the placebo group with no differences in the total UPDRS score between the two groups during the investigation. The ESS was significantly improved at the end of week 6 compared with the baseline and the placebo group. Laboratory test results indicated there were no side effects in either group. Conclusion . The findings of LSF treatment have clear clinical effects in patients with sialorrhea and frequent overnight urination. LSF thus appears to be a potential choice as an additional drug that can improve the sialorrhea and frequent overnight urination symptoms of PD patients.